Study of Seismic Performance of Vertical Irregular Structure with Glass Fiber Reinforced Shear wall (Universal Technical Journal of Lumbini International Academy of Science and Technology, 2025)
At present days building a structure with all the regular configurations is not feasible in most of the cases due to the irregular plot dimensions, aesthetic visual and functional requirements in the urban cities. The structures with more irregular configuration either horizontally or vertically are more vulnerable to earthquake. Such vertical irregularity stabilized by providing Shear wall. GFRP bars are light weight, ductile and noncorrosive in nature so GFRP bars were used in shear wall. So, this study aims to find out seismic response of vertical irregular building with GFRP shear wall under seismic load. The setback at both sides building with GFRP shear wall at corner analyzed using Response spectrum analysis method using NBC 105:2020 and ACI 440 1R 2006 code on ETABS software. It found that percentage of decrease of displacement with GFRP shear wall 39.52% and 37.98% in X and Y-direction respectively, percentage of decrease of drift with GFRP shear wall 44.79% and 43.43% in X and Y-direction respectively and Base shear increased by 2.42%.